Comparison of static and dynamic models of maternal immunization to prevent infant pertussis in Brazil. Issue 1 (3rd January 2021) - Russell, Louise B.; Kim, Sun-Young; Toscano, Cristiana; Cosgriff, Ben; Minamisava, Ruth; Lucia Andrade, Ana; Sanderson, Colin; Sinha, Anushua
Highlights: Dynamic transmission models of infectious disease capture the herd immunity effects of vaccination. We compared dynamic and static models of maternal acellular pertussis (aP) immunization built with Brazilian data. At infant vaccine coverage < 90–95%, both models estimate that maternal immunization is cost-effective. Only the dynamic model shows that maternal immunization is not cost-effective at infant coverage > 90–95%. The background effect of routine infant vaccination is critical to the cost-effectiveness of maternal aP immunization. Abstract: Background: This paper compares cost-effectiveness results from two models of maternal immunization to prevent pertussis in infants in Brazil, one static, one dynamic, to explore when static models are adequate for public health decisions and when the extra effort required by dynamic models is worthwhile. Methods: We defined two scenarios to explore key differences between static and dynamic models, herd immunity and time horizon. Scenario 1 evaluates the incremental cost/DALY of maternal acellular pertussis (aP) immunization as routine infant vaccination coverage ranges from low/moderate up to, and above, the threshold at which herd immunity begins to eliminate pertussis. Scenario 2 compares cost-effectiveness estimates over the models' different time horizons. Maternal vaccine prices of $9.55/dose (base case) and $1/dose were evaluated. Results: The dynamic model shows that maternal immunization could be cost-saving as well as life-saving at low levels of infant vaccination coverage. When infant coverage reaches the threshold range (90–95%), it is expensive: the dynamic model estimates that maternal immunization costs $2 million/DALY at infant coverage > 95% and maternal vaccine price of $9.55/dose; at $1/dose, cost/DALY is $200, 000. By contrast, the static model estimates costs/DALY only modestly higher at high than at low infant coverage. When the models' estimates over their different time horizons are compared at infant coverage < 90–95%, their projections fall in the same range. Conclusions: Static models may serve to explore an intervention's cost-effectiveness against infectious disease: the direction and principal drivers of change were the same in both models. When, however, an intervention too small to have significant herd immunity effects itself, such as maternal aP immunization, takes place against a background of vaccination in the rest of the population, a dynamic model is crucial to accurate estimates of cost-effectiveness. This finding is particularly important in the context of widely varying routine infant vaccination rates globally. Clinical Trial registry: Clinical Trial registry name and registration number: Not applicable.